POPULATION STRUCTURE AND BIOREPRODUCTION OF BIGEYE TUNA (Thunnus obesus) IN WESTERN PART OF SUMATERA AND SOUTHERN PART OF JAVA AND NUSA TENGGARA, INDIAN OCEAN - Ali Suman; Hari Eko Irianto; Khairul Amri; Budi Nugraha; Gatut Bintoro (Research Center for Fisheries, 2015)
Bigeye tuna is an important fish resource in the Indian Ocean. This species like other tuna species needs to be managed properly in both national and international levels. Therefore some data and information on population structure and bioreproduction are required for management purpose. The current research was conducted to identify the population structure and bioreproduction of bigeye tuna (Thunnus obesus) in west off Sumatera and south off Java and Nusa Tenggara of Indian Ocean where tuna fishing spots are important. This research was based on catch landed by fishermen from the Indian Ocean during 2010. Analysis of population structure was done using DNA genetic analyses and bioreproduction by using histology technique. Results show that the population structure of the bigeye tuna in the Indian Ocean consisted of two different sub populations namely sub population of west off Sumatra and sub population of south of Java and Nusa Tenggara waters. Most of catch (about 39%) was categorized as immature fish (GI I). The immature fish was mostly found in west off Sumatera waters, meanwhile the catch in south off Java and Nusa Tenggara waters was mostly categorized as mature fish. This result may indicate that south off Java and Nusa Tenggara waters is a spawning ground of the bigeye tuna.